2006
DOI: 10.1167/iovs.05-0895
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Spectacle-Wear Compliance in School-Aged Mexican Children

Abstract: Compliance with spectacle wear may be very low, even when spectacles are provided free of charge, particularly among older, urban children, who have been shown in many populations to have the highest prevalence of myopia. As screening programs for refractive error become increasingly common throughout the world, new strategies are needed to improve compliance if program resources are to be maximized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
189
5
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 143 publications
(214 citation statements)
references
References 24 publications
18
189
5
2
Order By: Relevance
“…free glasses 3,6,7 and educational interventions to promote spectacle wear 3,12 have generally shown low uptake, the current report demonstrated that free glasses combined with education on their use and a teacher incentive maintained wear in between two-thirds and 90% of children needing them over the course of a school year. The impact of the intervention on spectacle wear at 6 months was greater than that of family wealth, parental spectacle wear, and children's uncorrected VA. Our main study outcome, observed wear at the time of an unannounced examination, might be expected to underestimate true daily use of spectacles somewhat.…”
Section: Whereas Previous Studies Of Programs Providingmentioning
confidence: 57%
See 2 more Smart Citations
“…free glasses 3,6,7 and educational interventions to promote spectacle wear 3,12 have generally shown low uptake, the current report demonstrated that free glasses combined with education on their use and a teacher incentive maintained wear in between two-thirds and 90% of children needing them over the course of a school year. The impact of the intervention on spectacle wear at 6 months was greater than that of family wealth, parental spectacle wear, and children's uncorrected VA. Our main study outcome, observed wear at the time of an unannounced examination, might be expected to underestimate true daily use of spectacles somewhat.…”
Section: Whereas Previous Studies Of Programs Providingmentioning
confidence: 57%
“…3,6,7,[23][24][25] Observed rates of wear were low, ranging from 13% to 41%. 3,6,7,21,23,24 All of the few studies reporting higher rates (46% by Keay and associates in China, 25 56% by Vincent and associates in Thai refugee camps, 22 and 58% by von-Bischhoffshaussen and associates in Chile 20 ) relied on self-report and/or estimates of teachers or parents, 20,22 and had low (58%-76%) rates of follow-up 20,22 or assessment times as short as 1 month after spectacle distribution. 25 It would appear that longer-term (over the course of a school year) compliance with free spectacles, as measured by objective indicators such as observed wear at unannounced examinations, is low among children without additional interventions.…”
Section: Whereas Previous Studies Of Programs Providingmentioning
confidence: 99%
See 1 more Smart Citation
“…The dictionary (The Oxford Concise Dictionary) meaning of compliance refers to "Obedience to a request or command", in respect to our study, we used to prescribe for spectacles but it is useful only at time when child patients are wearing them. Refractive errors are commonly found as the causative agent for visual impairment in the most surveyed population and this impairment is easily treatable (1)(2)(3)(4)(5)(6)(7) . Previous studies shows prevalence of refractive error differs with geographic location, age, gender, education level, and amount of near work (1)(2)(3)(4)(5)(6)(7) .…”
Section: Introductionmentioning
confidence: 99%
“…Refractive errors are commonly found as the causative agent for visual impairment in the most surveyed population and this impairment is easily treatable (1)(2)(3)(4)(5)(6)(7) . Previous studies shows prevalence of refractive error differs with geographic location, age, gender, education level, and amount of near work (1)(2)(3)(4)(5)(6)(7) . Moderate hyperopia can be overcome by accommodation and many school aged children are most commonly found with myopic errors, these conditions have significance in economic, educational effectiveness including poor academic performance, reduced school performance, and social activity (5) .…”
Section: Introductionmentioning
confidence: 99%